(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
This paper reports the findings of a clinical study of a herbal preparation of Aspilia africana (Pers.) C.D. Adams against malaria, corroborated by in vitro antiplasmodial and cytotoxicity tests. In a non-controlled prospective design, 15 patients with uncomplicated malaria were administered with the herbal preparation and assessed for clinical manifestations of malaria, parasitaemia and global quality of life using the Kanorfsky Performance Scale. Antiplasmodial activity of extracts against the chloroquine-resistant strain of Plasmodium falciparum Dd2 was determined using the [3H]-hypoxanthine radioactive method while cytotoxicity against human urinary bladder carcinoma (ECV-304) and human hepatocellular carcinoma (HepG2) cell lines was determined using the MTT assay. Remarkable clinical improvements occurred 3 to 21 days after initiation of treatment. Forty nine days after starting treatment, all 15 patients had complete resolution of malaria symptoms and were cleared of parasitaemia and attained a Karnofsky Performance score of 100. The petroleum ether/ethyl acetate extract possessed in vitro antiplasmodial activity (IC50 30µg/ml) but no remarkable cytotoxicity. The A. africana preparation shows potential as an alternative for the management of uncomplicated malaria.